Towards Distributed Geolocation for Large Scale Disaster Management - Rosas-Olivos, E; Hidalgo-Castillo, N (IEEE Computer Society, 2016)
In the aftermath of major disasters such as earth-quakes, locating individuals is crucial for passing on vitalinformation, for example warnings and safety announcements. However, large scale disasters cause extensive damage to thenetwork infrastructures and a generalized loss of communicationsin the chaos that ensues. This position paper presents a prelim-inary study for a geolocation service that relies on inter-deviceconnections: mobile devices exchange positions of previouslyencountered devices when they come into contact. Every devicethus builds a partial map of device locations and can use it toenforce geographic routing protocols that are resilient to largescale disasters. © 2014 IEEE.